Die Stadt Kumasi (Ghana): Stadt und Umland in ihren funktionalen Beziehungen - Manshard, Walther (ERDKUNDE, 1961)
This paper attempts to give an account of the pattern of functional relationships and connections of Kumasi, one of the leading towns in West Africa. After a brief outline of Kumasi’s historical development as the old traditional capital of Ashanti, its importance as a regional centre of administrative, social, cultural, and commercial functions is investigated. While in West Africa industrialisation is only just beginning on a very limited scale, trade is the base of economic life for most major towns. Kumasi benefited at the same time from its importance as a central market of the Ashanti cocoabelt. A delimitation of the various urban spheres of influence (here denoted as Umland, Hinterland and Einflußgebiet) according to the varying degree of intensity of their functional relations with the centre, is suggested and interpreted. In this connection the close traditional links of parts of Ahafo with Kumasi are noteworthy. The recent (1958) attempt by the Ghana Government to diminish the importance of Ashanti by creating a Brong-Ahafo-Region, with Sunyani as a capital, is commented upon, since this accentuates the old contrast between the inner circle of the true Ashanti states (Tordoff, 1959) and the outer ring of losely associated states that were originally brought into the Confederacy by conquest and which have from time to time asserted their independence. In the absence of statistical work using modern com puting techniques Figs. 2, 3, 5, 6, 7 are based on field-work and enquiries by the author and students (1953-1959). They also give an idea of the urban field of towns of lesser central importance in and just outside Ashanti. Since this is former British territory a comparison with Smailes’s (1944) index for urban services proved interesting. Compared with other African territories, this part of the closed forest belt of Ghana, which also covers important cocoa growing areas, has a fairly well developed network of services. Discussing the influence of administrative divisions on the growth of urban settlements, the consequences of the creation of Brong-Ahafo on both Sunyani and Kumasi may well be worth studying in future. While Sunyani, no doubt, will expand, it is suggested that Kumasi has reached a size where any repercussions will not be very noticeable. Historically, the political relationships between Kumasi and the coastal capital of Accra is also briefly considered. The recent strong opposition of some Ashanti, particu larly based on Kumasi, brings to memory the old conflicts of the 19 th century between the British Colonial Government established on the coast and martial Ashanti in the hinterland. In countries such as Ghana geographical documentation of this sort seems to have some importance for the better understanding and planning of these agglomerations urbaines. In fact, many West African cities have the characteristics of boom towns, where the actual growth has outstripped the provision of adequate urban services (e. g. water-supply, electricity, housing, road building etc.). With its historical tradition as the main centre of communications and commerce, having one of West Africa’s biggest markets, Kumasi truly reflects the spectacular development of tropical Africa in the past 20 years. In the natural regional uniformity of the forest belt and the adjoining savanna woodlands, and with the absence of smaller regional units, as we experience them, for instance, in Europa, the understanding of functional relations, linking people of different tribal origin, has a special importance for Africa. It is from these contacts that a new national, regional or urban consciousness may result.